PENGARUH LOKASI, KUALITAS PELAYANAN, DAN FASILITAS HOTEL TERHADAP KEPUTUSAN MENGINAP PELANGGAN DI HOTEL (Survei pada The Margangsa Hotel Surakarta) - Suci, Gadis Prasetiya; Triastity, Rahayu; Sumaryanto, Sumaryanto (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2018)
The purpose of this research is to analyze the significance of the influence of the location, quality of service and hotel facilities partially or simultaneously against the decision of stay at The Margangsa Hotel. Technique of data analysis used the test of validity, reliability test, test the assumptions of classical linear regression, and multiple, t test, F test and coefficient of determination. The research results obtained conclusions that: there is a significant influence of the location of stay at The Margangsa Hotel Surakarta, meaning that if the strategic location of the hotel and easily accessible, then it can improve decisions. There is a significant influence on the quality of service of the decision of the stay at The Hotel Margangsa, Surakarta, meaning that if the quality of service received satisfactory, then customers can improve decisions. There is a significant influence on the facilities of stay at The Margangsa Hotel Surakarta, which means that if a full hotel facilities in accordance with the customer's needs then it can improve decisions. There is a significant influence of the location, quality of service and hotel facilities simultaneously against the decision of stay at The Margangsa Hotel.Keywords: location, service quality, hotel facilities, the decision to stay.